Pengembangan Sistem Pemesanan Antrian Pangkas Rambut Berbasis Web menggunakan Metode Rational Unified Process (RUP) pada Pangkas Rambut Danoe - Aris Aryanto; Yulia Ery Kurniawati (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to develop a web-based barbering system for Danoe barbershop. With the creation of this application, you can avoid queues at Danoe's barbershop which can cause the spread of COVID-19 and also make it easier for Mr. Danoe to manage customer data. This application has features for booking queues, displaying open or closed schedules, displaying opening and closing hours, displaying price lists, and managing customer data. The method used to build this application is the Rational Unified Process (RUP) method. This test is carried out using Black Box Testing and User Experience. This study resulted in a web-based queuing ordering system in order to avoid queues at Danoe Barbershop.